2013
DOI: 10.1111/dote.12122
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine oleate as a novel therapy is effective in resistant idiopathic achalasia

Abstract: Idiopathic achalasia (IA) is a primary motor disorder of the esophagus. Recently, ethanolamine oleate (EO) has been introduced as a novel therapy in IA. We investigate the long-term efficacy of EO injection in the selected IA patients. Two hundred twenty patients with IA were evaluated prospectively. Thirty-one patients who were resistant to or poor candidate of pneumatic balloon dilation and/or cardiomyotomy were enrolled in this study. EO was injected into the lower esophageal sphincter three times at 2-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“… 10 15 New options for achalasia peroral endoscopic myotomy (POEM), self-expanding metal stents, endoscopic sclerotherapy have shown promising results but there are only a few prospective observational studies to support their efficacy. 15 23 Current standard of care for achalasia includes forceful pneumatic dilation/balloon dilatation (PD/BD) and laparoscopic (Heller’s) esophageal myotomy (LEM) with or without an anti-reflux procedure. 15 There are some randomized controlled trials (RCTs) comparing the success rate (improvement of dysphagia) of these procedures at short-term follow-up, 8 , 24 26 but there are only 3 RCTs comparing the long-term outcomes at 5 years published till date.…”
Section: Introductionmentioning
confidence: 99%
“… 10 15 New options for achalasia peroral endoscopic myotomy (POEM), self-expanding metal stents, endoscopic sclerotherapy have shown promising results but there are only a few prospective observational studies to support their efficacy. 15 23 Current standard of care for achalasia includes forceful pneumatic dilation/balloon dilatation (PD/BD) and laparoscopic (Heller’s) esophageal myotomy (LEM) with or without an anti-reflux procedure. 15 There are some randomized controlled trials (RCTs) comparing the success rate (improvement of dysphagia) of these procedures at short-term follow-up, 8 , 24 26 but there are only 3 RCTs comparing the long-term outcomes at 5 years published till date.…”
Section: Introductionmentioning
confidence: 99%
“…Only minor adverse events occurred in this trial, and the authors concluded that EO injection could safely be used in the treatment of resistant idiopathic achalasia. 11 A small group of patients (nine patients) with achalasia were treated with the combined therapy (250 units of Dysport followed 7 days later with PBD). They were followed every 3 months, and the longest symptom improvement was 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…A standard questionnaire was used for calculating the achalasia symptom score (ASS) as in our previous studies. 12 , 13 The severity of each symptom was recorded on a scale of 0 to 3, depending on its frequency. The total symptom score was the sum of five cardinal symptoms scores and the severity score of dysphagia ( tables 1 , and 2 ).…”
Section: Methodsmentioning
confidence: 99%